Migration: from development to sustainable development, new agenda and analysis of theoretical aspects - Leila F. Delovarova; Svetlana N. Mishchuk (Наука. Культура. Общество, 2022)
Migration and development issues are becoming increasingly important and controversial in modern migration research. This is primarily due to the increasing global and regional mobility and its influence on the transformation processes of the modern system of international relations. Analysis of the relationship between migration and development, and today we are talking about sustainable development, as a new theoretical structure and practical approach are relevant and require the development of new research. This is especially important in the context of the 17 Sustainable Development Goals and processes related to the globalization of migration, labor markets, the increasing role of economic aspects and the development of regional and global cooperation.